Percutaneous tracheostomy in COVID-19 patients: The Miami model (2020)
The surge in critically ill patients requiring mechanical ventilation fueled by the COVID-19 pandemic has strained healthcare systems globally. With the increasing need for critical care resources, tracheostomy can facilitate weaning from mechanical ventilation and potentially increase availability of critical care resources. In this case series of three patients, we describe our technique for performing bedside percutaneous tracheostomy on patients with persistently positive SARS-CoV-2 real time polymerase chain reaction (RT-PCR). We hope to provide proceduralists with a specific method for percutaneous tracheostomies that is both safe for the patient and provider.